International migration and "educated unemployment" - Oded Stark; C. Simon Fan (University of Warsaw, Centre of Migration Research (CMR), 2006)
This paper provides a novel explanation of 'educated unemployment,' which is a salient feature of the labor markets in a number of developing countries. In a simple job-search framework we show that 'educated unemployment' is caused by the perspective of international migration, that is, by the possibility of a 'brain drain.' In addition, the analysis shows that a developing country may end up with more educated workers despite the brain drain and educated unemployment.
Keywords: F22; J24; J61; J64; O15; 330; International migration; Human capital formation; "Educated unemployment"; Beneficial brain drain; Arbeitsmigranten; Brain Drain; Humankapital; Arbeitslosigkeit; Hochqualifizierte Arbeitskräfte; Theorie